Effects of higher and more frequent dosing of alglucosidase alfa and immunomodulation on long‐term clinical outcome of classic infantile Pompe patients - Poelman, Esther (J Inherit Metab Dis, 2020)
The aim of this study was to compare the long‐term outcome of classic infantile Pompe patients treated with 20 mg/kg alglucosidase alfa every other week (eow) to those treated with 40 mg/kg/week, and to study the additional effect of immunomodulation. Six patients received 20 mg/kg eow and twelve 40 mg/kg/week. Five patients were cross‐reactive immunologic material (CRIM)‐negative, two in the 20 mg, three in the 40 mg group. We compared (ventilator‐free) survival, motor outcome, infusion associated reactions (IARs), and antibody formation. From 2012 on patients >2 months in the 40 mg group also received immunomodulation with rituximab, methotrexate, and intravenous immunoglobulin (IVIG) in an enzyme replacement therapy (ERT)‐naïve setting. Survival was 66% in the 20 mg group and 92% in the 40 mg group. Ventilator‐free survival was 50% and 92%. Both CRIM‐negative patients in the 20 mg group died, whereas all three are alive in the 40 mg group. In the 20 mg group, 67% learned to walk compared with 92% in the 40 mg group. At the age of 3 years, 33% and 92% were able to walk. Peak antibody titers ranged from 1:1250 to 1:31 250 in the 20 mg group and from 1:250 to 1:800 000 in the 40 mg group. Five patients of the 40 mg group of whom two CRIM‐negative also received immunomodulation. B‐cell recovery was observed between 5.7 and 7.9 months after the last dose of rituximab. After B‐cell recovery titers of patients with and without immunomodulation were similar (ranges 1:6 250‐1:800 000 and 1:250‐1:781 250). This study shows that classic infantile patients treated with 40 mg/kg/week from the start to end have a better (ventilator‐free) survival and motor outcome. Immunomodulation did not prevent antibody formation in our study.